Development of Dentofacial Anomalies Associated with Airway Obstruction and Low Tongue Posture - Shcherbyna, Tetyana; Lykhota, Kostiantyn (Actual Dentistry, 2026)
Aim: To assess the impact of low tongue posture on the development of Angle Class III dentoskeletal anomalies and to evaluate the clinical effectiveness of a combined approach involving myofunctional therapy and orthodontic appliance treatment in pediatric patients. Materials and Methods: This prospective observational study enrolled 100 children (55 girls and 45 boys), aged 5–14 years. Diagnostic cephalometric analysis was performed to categorize participants into two groups: (1) functional anterior mandibular displacement (dentoalveolar Class III) and (2) skeletal Class III associated with maxillary retrognathia. Group 1 received EF Line functional appliances combined with targeted myogymnastics and breathing exercises. Group 2 underwent rapid maxillary expansion and facemask therapy, followed by myofunctional exercises. Clinical endpoints included the restoration of nasal breathing, normalization of craniofacial parameters according to cephalometric indices, and relapse prevention. Outcomes were assessed upon treatment completion and at a six-month follow-up. Results: Significant improvements were observed across all clinical and cephalometric measures. The restoration of nasal breathing occurred in over 85% of subjects. The mean maxillary width increased by 2.3 mm (±0.8) in Group 2, with a corresponding improvement in the maxillary position and a reduction in mandibular prognathism. Group 1 achieved the normalization of dental occlusion in 80% of cases. The addition of myofunctional therapy was associated with a relapse rate of less than 10% at the six-month follow-up period. Conclusions: A multimodal intervention combining orthodontic appliance therapy and myofunctional exercises is effective in the early correction of Class III dentofacial anomalies associated with low tongue posture and airway obstruction. This approach results in both functional and skeletal improvements with a low relapse incidence. Such interdisciplinary interventions should be considered in pediatric orthodontic practice to prevent the progression of Class III malocclusion.